Perancangan Sistem Informasi Pengelolaan Pakan Ternak Berbasis Web Menggunakan Metode Waterfall - Hizki Alawiyah; Bayu Pamungkas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Animal feed management plays a crucial role in supporting the smooth operation of livestock farms, particularly in government agencies involved in livestock development and breeding. The Margawati Sheep and Goat Livestock Breeding Development Center (BPPTDK) still employs manual feed data management processes, from recording feed types, stock management, to report preparation. This situation results in a suboptimal data management process due to the potential for recording errors, delays in information delivery, and difficulties in accurately monitoring feed stocks. This study aims to design a Web-Based Animal Feed Management Information System to support a more effective, integrated, and computerized feed data management process. The system development method used is the Waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The system design process was carried out using the Unified Modeling Language (UML) in the form of use case diagrams, activity diagrams, and class diagrams. The results of the study indicate that the developed system is able to assist in managing feed type data, controlling feed stock, recording incoming and outgoing feed data, and preparing reports more effectively compared to the previous manual system. Test results using the Black Box Testing method indicate that all the system's main functions operate according to user requirements. The designed system also supports real-time feed stock monitoring and facilitates integrated data management according to operational requirements at the Margawati BPPTDK UPTD. Therefore, the developed information system is expected to improve the effectiveness and efficiency of the livestock feed management process in a sustainable manner.